Peningkatan Keterampilan Menulis Puisi Menggunakan Media Gambar dan Video Pada Siswa Kelas VA SD Muhammadiyah 22 Sruni Surakarta Tahun 2015/2016 - ANISAH, Anisah (2016)
The purpose of this research is to improve the skills of writing poetry in the fifth grade students of SD Muhammadiyah Surakarta Sruni 22. Learning by using media images and videos selected to give a different feel in learning activities, assist students in determining their imagination vocabulary or diction. The study was conducted in two cycles so that more optimal results. Subjects in this study were students in grade 22 Sruni VA SD Muhammadiyah Surakarta with 40 students, consisting of 24 female students and 16 male students. The research was conducted from October to January 2016. The data collection technique used was through observation, tests and interviews. Based on the data obtained are in accordance KKM is 13 people or 32.5%, whereas that is not in accordance with the KKM is 27 people or 67.5%. The average score writing poetry in the first cycle is 78.30. The score in the second cycle showed an increase of cycle I. Students who obtain the value of ≥75 is 39 children and students who received grades ≤75 is 1 child. So students who received grades ≥75 is 97.5%, while the students who have not met the KKM contained 2.5% of the total number of students. The average value of free poetry writing students in the second cycle to increase from the first cycle, ie from 78.30 into 79.05. It can be concluded that the learning activity meets the criteria of success. And it can be said that the media images and video can improve the students' writing skills puisis.